An overview of experimental simulations of microbial activity in early Earth - Zhao, Mingyu; Zhao, Yao; Lin, Wei; Xiao, Ke-Qing (Frontiers in Microbiology, 2023)
Microbial activity has shaped the evolutions of ocean and atmosphere throughout the Earth history. Thus, experimental simulations of microbial metabolisms under environment conditions of the early Earth can provide vital information regarding the biogeochemical cycles and the interaction and coevolution between life and environment, with important implications for extraterrestrial exploration. In this review, we discuss the current scope of and knowledge on the experimental simulations of microbial activity in environments mimicking those of early Earth, with perspective on future studies. Inclusive experimental simulations involving multiple species, and cultivation experiments with more constraints on environmental conditions close to early Earth will significantly advance our understanding of the biogeochemical cycles of the geological past.